Cost-effectiveness analysis: role and implications. (March 2013) - Marsden, G; Wonderling, D
Background: Cost-effectiveness analysis (CEA) is often misperceived to be a cost-cutting exercise. The intention of CEA is not to identify and implement cheap technologies, but rather those which offer maximum health gain, subject to available funds. Such analysis is crucial for decision making in health care, as tight budget constraints mean spending in one area of healthcare displaces spending elsewhere. Therefore in order to achieve the greatest health gain for the overall population, treatments must be selected which provide the greatest health gain within the available funds. Summary: The relevance of CEA in health care systems is explained, using varicose vein treatment in the UK NHS as an example. Treatment for varicose veins is often not commissioned to at a local level, most likely because it is misperceived to be a cosmetic problem. However, this view does not take into account the impact of quality of life. CEA balances costs against a quantitative measure of health related quality of life, and could therefore be used to determine whether it is cost-effective to provide varicose vein treatment. The current literature on the cost-effectiveness of varicose vein treatment is reviewed, and an overview of cost-effectiveness principles is provided. Concepts such as economic modelling, incremental cost-effectiveness ratios (ICERs), net monetary benefit (NMB) and sensitivity analysis are explained, using examples relevant to varicose veins where appropriate. Conclusion: This article explains how, far from cutting costs and sacrificing patient health, CEA provides a useful tool to maximise the health of the population in the face of ever tightening budget constraints. CEA could be used to compare the cost-effectiveness of the various treatment options for varicose veins, and efficiencies realised.